Strategi Penyuluh Agama dalam Meningkatkan Ekonomi Kreatif Remaja Pada Era Revolusi Industri 4.0 di Kabupaten Sumbawa - Khoirur Roji'in (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2022)
Abstract This study aims to find out the steps that religious counselors do to improve the creative economy of adolescents in Sumbawa, with the supporting and inhibiting factors. This study uses a qualitative descriptive approach, with data collection techniques used observation, interviews, and documentation. The results showed that (1) The steps of religious counselors do in improving the creative economy of adolescents in Sumbawa, were to build relationships or approaches to the community that aimed to establish good communication in order to create a conducive situation, religious counselors in carrying out their duties in inviting, calling, and can convince teenagers to manifest religious behavior and hold a creative economic development process for the target group (weekly coaching). This step is the right step and must be developed, in order to foster youth into Islamic youth, and have an entrepreneurial spirit. (2) The supporting factors for religious counselors in improving the creative economy of youth in Sumbawa are support from the community and adequate facilities and infrastructure, as well as motivation from teenagers. The inhibiting factors are the lack of religious counselors, namely there are only a few people in one village and have to carry out activities, as well as the lack of discipline and seriousness of teenagers, and teenagers who are ignorant.